World Enough and Time - Senior, W. A. (Hungarian Journal of English and American Studies, 2022)
Book review:Morse, Donald E. It’s Time: A Mosaic Reflecting What Living in Time is Like. Debrecen: Debrecen UP, 2022. 326 pages. ISBN 978-963-615-004-4. Open Access E-book and Pbk. HUF 4,000.